33‐1: Invited Paper: Liquid Crystals for Virtual Reality (VR). Issue 1 (28th June 2021) - Peng, Fenglin; Geng, Ying; Wang, Junren; Lu, Lu; Zhao, Yang; Maimone, Andrew; Gao, Weichuan; Huang, Yuge; Gollier, Jacques; Silverstein, Barry
Abstract : Liquid crystal has been widely used in display applications, including Augmented Reality (AR) and Virtual Reality (VR) headset. In this paper, we discuss how liquid crystal technology can enable a virtual reality (VR) headset with glass‐type form factor, better image quality, and wearing comfort.